4(x-5)=2(2x-7)+6

Simple and best practice solution for 4(x-5)=2(2x-7)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-5)=2(2x-7)+6 equation:



4(x-5)=2(2x-7)+6
We move all terms to the left:
4(x-5)-(2(2x-7)+6)=0
We multiply parentheses
4x-(2(2x-7)+6)-20=0
We calculate terms in parentheses: -(2(2x-7)+6), so:
2(2x-7)+6
We multiply parentheses
4x-14+6
We add all the numbers together, and all the variables
4x-8
Back to the equation:
-(4x-8)
We get rid of parentheses
4x-4x+8-20=0
We add all the numbers together, and all the variables
-12!=0
There is no solution for this equation

See similar equations:

| 2(x–2)=50 | | Y-(-2)=-(x-4) | | 5y–1=5y+1 | | 7x+30=4x+7=180 | | 9.15=y+5 | | 3(x-4)+2(x+1)=5x-11 | | 4e+24=4X10^24 | | 4+8h=9h−6 | | y=-125+600 | | 3x+14+122.5=180 | | 5-2/3x=1/2x+-4 | | 7=c+37/7 | | -1r=-225 | | 15(2(x-1)=15(2(x+1) | | 24.7=y/12 | | 8x-6=2(x-3)+6 | | 4x−3=2x+7 | | 15u=6u+81 | | 26=12x | | Y-4=x-7 | | 2+a/4=-1+7 | | u÷5=4. | | 5x+32=3x-8 | | 8x+2=-6x-10 | | 7x+15=2(3x+18)+x | | 394z+4)=36 | | -98=4(-6-6r)-2 | | 53.2=19/z | | -5k-2=-7k | | x/3+2x/6=1/3 | | 310​=(−25​)x​ | | (x-16^2)=256 |

Equations solver categories